Reliability and validity of the Sidaamu Afoo version of the pelvic organ prolapse symptom score questionnaire - Melese Siyoum; Wondwosen Teklesilasie; Rahel Nardos; Biniyam Sirak; Ayalew Astatkie (BMC, 2023)
Abstract Background Both for clinical and research purposes, it is critical that clinicians and researchers use a tool that is trans-culturally adapted and tested for its psychometric properties. The English version of the Pelvic Organ Prolapse Symptom Score (POP-SS) questionnaire was developed in 2000. Since then it has been translated into other languages and verified. However, the tool has not been adapted for use in Sidaamu Afoo language in the Sidama Region of Ethiopia. Objective This study aimed to translate and adapt the Pelvic Organ Prolapse Symptom Score questionnaire into Sidaamu Afoo and evaluate its psychometric properties. Methods A total of 100 women with symptomatic prolapse completed version-2 of the POP-SS questionnaire during the first round of interviews, and 61 of them completed the questionnaire during the second round of interviews (to establish the test-retest reliability). We adapted the scale translation process recommended by Beaton and his colleagues. The content validity was assessed using the content validity index and the construct validity was done based on exploratory factor analysis using the principal component analysis model. The criterion validity was evaluated by using the Kruskal-Wallis test based on stages of the prolapse established via pelvic examination. The internal consistency reliability of the scale was assessed using Cronbach's alpha value, and test-retest reliability was evaluated using the intraclass correlation coefficient. Results The questionnaire was successfully translated to Sidaamu Afoo, and achieved a good content validity index (0.88), high internal consistency (Cronbach's alpha of 0.79), and test-retest reliability (an intraclass correlation coefficient of 0.83). The exploratory factor analysis revealed two factors based on an eigenvalue of 1. The two factors explained 70.6% of the common variance, and each item loaded well (0.61 to 0.92) to its corresponding factor. There is a significant difference in the median score of prolapse symptoms across different stages of prolapse (Kruskal-Wallis χ2, 17.5, p < 0.001). Conclusion The Sidaamu Afoo version of the POP-SS tool is valid and reliable. Further studies that involve a balanced number of women in each stage of prolapse are needed to avoid the ceiling and floor effects.